2015
DOI: 10.31018/jans.v7i2.701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of higher salinities on growth and survival of pacific white shrimp, Litopenaeus vannamei (Boone, 1931)

Abstract: Abstract:The growth and survival of Litopenaeus vannamei post larvae was measured in controlled different salinities condition 35ppt (T1), 40ppt (T2), 45ppt (T3) and 50ppt (T4) were maintained. Group of Shrimp post larvae (weight 0.032 g ± 0.002) were stocked at a density of 35 nos. /aquarium in above salinity ranges. Animals were fed with commercial feed (35% Crude Protein) @ 5% of body weight four times a day. The results indicate that higher SGR was observed in T2 (1.99±0.08) followed by T1 (1.75±0.07), T3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…For systems with salinities slightly above the optimum, L. vannamei shows significant adaptation capabilities. Ayaz, Sumara, Vadher and Ishakani () reported good survival rates (100%–94.99%) and relatively similar SGR values ranging from 1.54 to 1.99 in systems with hypersaline water (35–45 g/L) in L. vannamei postlarvae reared 62 days. Robertson, Lawrence and Castille () reported that L. vannamei juvenile (5.3 g) reared 42 days achieved 17.5 ± 0.3 g at 46 g/L with a survival of 87%.…”
Section: Discussionmentioning
confidence: 90%
“…For systems with salinities slightly above the optimum, L. vannamei shows significant adaptation capabilities. Ayaz, Sumara, Vadher and Ishakani () reported good survival rates (100%–94.99%) and relatively similar SGR values ranging from 1.54 to 1.99 in systems with hypersaline water (35–45 g/L) in L. vannamei postlarvae reared 62 days. Robertson, Lawrence and Castille () reported that L. vannamei juvenile (5.3 g) reared 42 days achieved 17.5 ± 0.3 g at 46 g/L with a survival of 87%.…”
Section: Discussionmentioning
confidence: 90%
“…Sejak awal era industri, penyerapan CO2 oleh laut mengakibatkan meningkatnya pengasaman air laut dan suhu Cheung et al, (2016) Dalam hal ini perubahan iklim mampu memberikan efek perubahan pada suhu, pH air laut, dan salinitas. Suhu dan salinitas dianggap sebagai faktor signifikan dalam akuakultur (Ayaz et al, 2015;Pradhan et al, 2021). Perubahan suhu rata-rata dan curah hujan rata-rata mendorong perubahan iklim pada budidaya udang.…”
Section: Pendahuluanunclassified